2016
DOI: 10.1111/dme.13062
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of better management of glycaemic control in adults with Type 1 and Type 2 diabetes on the number of clinical complications and the associated financial benefit

Abstract: Aim To estimate potential cost avoidance through modest and achievable improvements in glycaemic control in adults with Type 1 or Type 2 diabetes mellitus in the UK healthcare system. MethodsThe IMS Core Diabetes Model was used to examine the impact of improved glycaemic control (indicated by reduction in HbA 1c level), in a representative cohort of adults with Type 1 or Type 2 diabetes. The cumulative incidence of microvascular and macrovascular complications was modelled across 5-year periods to a 25-year ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 14 publications
2
97
1
1
Order By: Relevance
“…In addition, improvements in glycemic control have a positive economic impact. Using the CORE Diabetes Model, it was shown that modest and achievable improvements in glycemic control generate significant reductions in the incidence and cost of microvascular complications 3. A cost avoidance of £340 million was estimated after 5 years of sustained glycemic control, increasing to £5.5 billion after 25 years for the UK 3.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, improvements in glycemic control have a positive economic impact. Using the CORE Diabetes Model, it was shown that modest and achievable improvements in glycemic control generate significant reductions in the incidence and cost of microvascular complications 3. A cost avoidance of £340 million was estimated after 5 years of sustained glycemic control, increasing to £5.5 billion after 25 years for the UK 3.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported to reduce the level of glycated haemoglobin level (HbA 1c ), a clinical measure of adequate control, by as much as 37% [8]. Having a lower HbA 1c value (≤7% or ≤53 mmol/mol) reduces the likelihood of developing micro- and macrovascular complications over time [9]. Despite the increasing evidence that supports the benefits of DSM, uptake remains low, especially in culturally diverse populations [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the health economic value of improved disease management in Type 2 diabetes 25, and estimated the potential costs avoided that a modest HbA 1c reduction would achieve within the UK healthcare system 7. In the present analysis, we quantified the health economic burden of inadequate Type 1 diabetes management in the UK, and estimated the value associated with incremental HbA 1c improvements, fewer hypoglycaemic events and reduced BMI in people with Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%